2016
DOI: 10.1038/nsmb.3151
|View full text |Cite
|
Sign up to set email alerts
|

Neil DNA glycosylases promote substrate turnover by Tdg during DNA demethylation

Abstract: DNA 5-methylcytosine is a dynamic epigenetic mark which plays important roles in development and disease. In the Tet-Tdg demethylation pathway, methylated cytosine is iteratively oxidized by Tet dioxygenases and unmodified cytosine is restored via thymine DNA glycosylase (Tdg). Here we show that human NEIL1 and NEIL2 DNA glycosylases coordinate abasic site processing during TET–TDG DNA demethylation. NEIL1 and NEIL2 cooperate with TDG during base excision: TDG occupies the abasic site and is displaced by NEILs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 67 publications
(95 reference statements)
4
94
2
1
Order By: Relevance
“…DOI 10.1002/em one study, substrate turnover by TDG was reportedly enhanced by the NEIL enzymes (Schomacher et al, 2016). DOI 10.1002/em one study, substrate turnover by TDG was reportedly enhanced by the NEIL enzymes (Schomacher et al, 2016).…”
Section: The Enigma Of Mtdna Methylationmentioning
confidence: 99%
“…DOI 10.1002/em one study, substrate turnover by TDG was reportedly enhanced by the NEIL enzymes (Schomacher et al, 2016). DOI 10.1002/em one study, substrate turnover by TDG was reportedly enhanced by the NEIL enzymes (Schomacher et al, 2016).…”
Section: The Enigma Of Mtdna Methylationmentioning
confidence: 99%
“…found that TDG operates in at ight complex with other enzymes such as TET1 [227] and interplays with the NEIL1/2 bifunctional glycosylases, [228] so that the formed abasic site may indeed be processed very quickly.…”
Section: Passive Demethylationmentioning
confidence: 99%
“…Moreover, increasing literature has further emphasized the importance of NEIL1's cellular repair activity, as NEIL1 deficiency has led to multiple abnormalities and is associated with severe human diseases, including cancer (14-19). Additionally, emerging evidence has also implicated a role of NEIL1 in active DNA demethylation (20)(21)(22).NEIL1 is capable of removing a wide array of oxidized pyrimidines and purines; representative substrates of extensive investigations include thymine glycol (Tg), 5-hydroxyuracil (5-OHU), 5-hydroxycytosine (5-OHC), dihydrothymine (DHT), and dihydrouracil (DHU), as well as the formamidopyridines (FapyA and FapyG), spiroiminodihydantoin (Sp), and guanidinohydantoin (Gh) (23-27). Among these lesions, Tg is the most common pyrimidine base modification produced under oxidative stress and ionizing radiation (28)-arising from oxidation of thymine and 5-methylcytosine-and is also a preferred substrate of NEIL1 (3).…”
mentioning
confidence: 99%
“…Moreover, increasing literature has further emphasized the importance of NEIL1's cellular repair activity, as NEIL1 deficiency has led to multiple abnormalities and is associated with severe human diseases, including cancer (14)(15)(16)(17)(18)(19). Additionally, emerging evidence has also implicated a role of NEIL1 in active DNA demethylation (20)(21)(22).…”
mentioning
confidence: 99%